The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.21595/jve.2017.18924
|View full text |Cite
|
Sign up to set email alerts
|

Multi-agent replicator controller for sustainable vibration control of smart structures

Abstract: Developed in the artificial intelligence community, an intelligent agent is an autonomous abstract or software entity that observes through sensors and acts upon an environment in an adaptive or intelligent manner. In a centralized control system, one central controller uses the global measurement data collected from all the sensors installed in the structure to make control decisions and to dispatch them to control devices. The centralized controller itself represents a single point of potential failure. To o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 48 publications
(54 reference statements)
1
27
0
Order By: Relevance
“…These are active, semi-active, and hybrid systems. [57] While active systems can effectively mitigate most of the disadvantages of conventional TMDs, with considerable recent improvements in their control algorithms to improve their response, [58][59][60][61][62][63][64][65][66] they typically result in a higher cost and require a large source of external power, which makes them less reliable and practical. To overcome this last detriment, semi-active systems are devised to require only a minimum amount of external energy.…”
Section: Conventional Approachesmentioning
confidence: 99%
“…These are active, semi-active, and hybrid systems. [57] While active systems can effectively mitigate most of the disadvantages of conventional TMDs, with considerable recent improvements in their control algorithms to improve their response, [58][59][60][61][62][63][64][65][66] they typically result in a higher cost and require a large source of external power, which makes them less reliable and practical. To overcome this last detriment, semi-active systems are devised to require only a minimum amount of external energy.…”
Section: Conventional Approachesmentioning
confidence: 99%
“…First, the definition of both the emotional and sensory signals such that they are able to represent the system's state and the control's objective. In the current problem, those stimuli signals are characterized through Equations (12) and (13). Secondly, one must be aware that the controller performance strongly depends on several parameters such as the amygdala and orbitofrontal learning rates.…”
Section: Control System Architecturementioning
confidence: 99%
“…Besides requiring less external energy, in general semi-active vibration control leads to increased overall stability compared to active control [1,2]. For those reasons, the use of semi-active control systems is a trending research theme and can be found applied in many distinct engineering areas such as vehicles suspensions and smart structures just to name a few [3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Gutierrez Soto and Adeli (2017a) introduced novel multiagent replicator controllers for sustainable vibration control of smart structures based on three ideas: artificial intelligence concept of agents, replicator dynamics from evolutionary game theory, and energy minimization.…”
Section: Other Adaptive Control Algorithmsmentioning
confidence: 99%